Low-Bandwidth Photonics-Assisted Receiver for Broad-Bandwidth Wireless Signals - Mohamed I. Hosni; Younus Mandalawi; Janosch Meier; Karanveer Singh; Ayman M. Mokhtar; Thomas Schneider (IEEE Access, 2023)
This paper introduces a photonics-assisted receiver that enables the reception of high-bandwidth wireless signals with low-bandwidth electronics. The receiver down-converts the input signal into parallel low-bandwidth sub-signals, employing photonics-based orthogonal sampling. This sampling is based on a multiplication and not switching, so, it does not introduce additional aperture jitter. Therefore, the photonics-assisted analog-to-digital converter (ADC) converts the wireless signal with a higher signal-to-noise-and-distortion ratio (SINAD), which improves the Q-factor for the detection. This Q-factor improvement is especially high, when the orthogonal sampling is carried out with low-jitter oscillators. Compared to the direct detection with 30 GHz, the simulation demonstrates a 2.2 dB Q-factor enhancement for the detection of a 30 GHz signal, with 10 GHz electronics. The same improvement is revealed in the experiment for the detection of 12 GHz signals with 4 GHz electronics.